Temporal Expression of Wnt1 Defines the Competency State and Terminal Identity of Progenitors in the Developing Cochlear Nucleus and Inferior Colliculus - Brown, Stephen; Zervas, Mark (Frontiers in Neuroanatomy, 2017)
The auditory system contains a diverse array of interconnected anatomical structures that mediate the perception of sound. The cochlear nucleus of the hindbrain serves as the initial site of convergence for auditory stimuli, while the inferior colliculus of the midbrain serves as an integration and relay station for all ascending auditory information. We used Genetic Inducible Fate Mapping (GIFM) to determine how the timing of Wnt1 expression is related to the competency states of auditory neuron progenitors. We demonstrate that the Wnt1 lineage defines progenitor pools of auditory neurons in the developing midbrain and hindbrain. The timing of Wnt1 expression specifies unique cell types during embryogenesis and follows a mixed model encompassing a brief epoch of de novo expression followed by rapid and progressive lineage restriction to shape the inferior colliculus. In contrast, Wnt1 fate mapping of the embryonic hindbrain revealed de novo induction of Wnt1 in auditory hindbrain progenitors, which is related to the development of biochemically distinct neurons in the cochlear nucleus. Thus, we uncovered two modes of lineage allocation that explain the relationship between the timing of Wnt1 expression and the development of the cochlear nucleus and the inferior colliculus. Finally, our analysis of Wnt1sw/sw mutant mice demonstrated a functional requirement of Wnt1 for the development of the auditory midbrain and hindbrain neurons. Collectively, our study provides a deeper understanding of Wnt1 lineage allocation and function in mammalian brain development.